Blood‐borne virus testing in emergency departments – a systematic review of seroprevalence, feasibility, acceptability and linkage to care. Issue 1 (14th June 2022) - Simmons, Ruth; Plunkett, James; Cieply, Lukasz; Ijaz, Samreen; Desai, Monica; Mandal, Sema
Abstract: Background: Blood‐borne viruses (BBVs) cause significant morbidity and mortality worldwide. Emergency departments (EDs) offer a point of contact for groups at increased risk of BBVs who may be less likely to engage with primary care. We reviewed the literature to evaluate whether BBV testing in this setting might be a viable option to increase case finding and linkage to care. Methods: We searched PubMed database for English language articles published until June 2019 on BBV testing in EDs. Studies reporting seroprevalence surveys, feasibility, linkage to care, enablers and barriers to testing were included. Additional searches for grey literature were performed. Results: Eight‐nine articles met inclusion criteria, of which 14 reported BBV seroprevalence surveys in EDs, 54 investigated feasibility and acceptability, and 36 investigated linkage to care. Most studies were HIV‐focused and conducted in the USA. Seroprevalence rates were in the range 1.5–17% for HCV, 0.7–1.6% for HBV, and 0.8–13% for HIV. For studies that used an opt‐in study design, testing uptake ranged from 2% to 98% and for opt‐out it ranged from 16% to 91%. There was a wide range of yield: 13–100% of patients received their test result, 21–100% were linked to care, and 50–91% were retained in care. Compared with individuals diagnosed with HIV, linkage to and retention in care were lower for those diagnosed with hepatitis C. Predictors of linkage to care was associated with certain patient characteristics. Conclusions: Universal opt‐out BBV testing in EDs may be feasible and acceptable, but linkage to care needs to be improved by optimizing implementation. Further economic evaluations of hepatitis testing in EDs are needed.